What Brazilian and Portuguese adolescents think about buying? - Lins, Samuel Lincoln Bezerra (2016)
Consumption and the acquisition of material goods play an important role in the life of people and mediaexposure of products has a particular influence on adolescent public. In order to identify the social representations of buyingin this age group, we asked 482 Brazilian adolescents and 238 Portuguese adolescents to express themselves on the word“buying” in a task of word association. The responses were analyzed by means of the program of textual data analysis Alcestethat extractedsix classes of words associated to products that are typical of the adolescent public, and classes related to aspectsof buying (emotional and cognitive) and to the buying environment. Sex belongingness and socioeconomic context also showedan effect on the formed representations.